STUDENTS’ CRITICAL THINGKING SKILLS AS REFLECTED ON THEIR IELTS READING TEST: CASE STUDY AT UNIVERSITY OF MUSLIM NUSANTARA AL-WASLIYAH - Reni Sapitri; Teguh Satria Amin (English Language Teaching and Research, 2018)
Critical reading has close links to EFL students’ competence in reading comprehension. Reading is one of the skills which encourage the readers to think critically in understanding the texts comprehensively without concerning on the written text itself. In the level of university specifically English education major, the aims of language learning is a mean of communication. It encourages the students to be able to understand the language concept in form of writing of various topics, explain the relationship and apply it by transforming the information or ideas with their own language. Thus, this research describes the critical thinking of the students as reflected on the IELTS reading test on the reading class. The respondents consisted of 25 students of English department from semester VII in 2017/2018 academic year in UMN Al-wasliyah. The research was conducted in qualitative in which the data were collected through reading test, observation, and interview. The findings recognize that critical reading skills are utmost importance for EFL students. However, many of them unable to apply relevant critical thinking skills in analyzing what they were reading. Keywords: Critical Thinking, Critical Reading, IELTS.